Canonical category „necessity” on the sacramental law in the Code of 1993 year - JANCZEWSKI, ZBIGNIEW (Prawo Kanoniczne, 2017)
In the Code of Canon Law in the part about sacraments baptism, con- rmation, Eucharist, penance and anointing of the sick there are canonical category “necessity”. is designation has ve kinds: necessity (regular), vera necessity, pastoral necessity, grave necessity, extreme necessity. In this article are analyses canonical norms inclusive those categories. Text shows a conditions since depend necessity also, for example illness, war, eart- hquake. On the end of article is denition of canonical category necessitas.